Pengaruh Penggunaan Chatbot dan Kepercayaan Konsumen Terhadap Minat Beli Konsumen Pada ShopeePT Renjana Adika Nusantara - Siti Amina; Ratih Amelia (Indonesian Journal of Islamic Economics and Business, 2026)
This study aims to analyze the effect of chatbot usage and customer trust on consumers’ purchase intention at Shopee PT Renjana Adika Nusantara. This research employed a quantitative method with descriptive and associative approaches. The sampling technique used purposive sampling with a total of 120 respondents who met the research criteria. Data were analyzed using the Partial Least Squares (PLS-SEM) method with the assistance of SmartPLS software. The results indicate that chatbot usage has a positive and significant effect on consumers’ purchase intention, suggesting that ease of obtaining information, responsiveness, and service effectiveness through chatbot features can increase consumers’ intention to purchase. Meanwhile, customer trust does not have a significant effect on purchase intention, indicating that trust in chatbot services has not become the primary factor influencing purchasing decisions. Furthermore, the research model shows moderate explanatory power, where chatbot usage and customer trust explain 50.6% of the variance in purchase intention, while the remaining 49.4% is influenced by other factors outside this study. The novelty of this research lies in examining the role of chatbot usage and customer trust in influencing purchase intention within the Shopee platform context at PT Renjana Adika Nusantara. These findings imply that companies should improve chatbot service quality to create a better consumer shopping experience.